Leaf spot on cattleya orchid caused by Neoscytalidium orchidacearum in Thailand - Nakarin Suwannarach (2018)
© 2018 The Canadian Phytopathological Society. Leaf spots caused by plant pathogenic fungi are among the main diseases affecting orchid plants worldwide. A leaf spot disease was widespread in a nursery of cattleya orchid (Cattleya lueddemanniana var. lueddemanniana) in Lampang Province, Thailand in 2016. A fungus was isolated from leaf lesions and identified as Neoscytalidium orchidacearum based on morphological characteristics and the identification was confirmed using a molecular phylogenetic analysis of the combined internal transcribed spacer and large subunit regions of ribosomal DNA sequences. The isolated fungus caused spot symptoms on inoculated orchid leaves similar to symptoms observed in the field. This is the first report of orchid leaf spot disease caused by N. orchidacearum.